A Review on Ruben’s Tube as Acoustic Propagator - R., Salim; Syed Tarmizi, Bin Syed Shazali; Sinin, Bin Hamdan; Magdalene, Anak Andrew Munot; A. M. A. A. M., Mohtar (UMP Publisher, 2018)
In 1905, Ruben’s Tube was invented by German physicists Heinrich Ruben and Otto Krigar-Menzel. The tube is closed at one end and the other end is attached with a loudspeaker, then filled with flammable gas. With the help of the Ruben’s Tube, the standing waves were represented physically by fire. There are no specific standards in which Ruben’s Tube is constructed. At certain resonance frequency, the flame produced visual standing wave that varies in height. It has been used in the teaching of acoustical resonance behavior. This article provides review on Ruben’s Tube and its operation, as well as some commentaries and drawbacks for each subtopic. Each of the journals that have similar setup have been reviewed to further explain the phenomena.